Original XPCTM Effect on Salmonella Typhimurium and Cecal Microbiota from Three Different Ages of Broiler Chickens When Incubated in an Anaerobic In Vitro Culture System - Park, Si Hong; Kim, Sun Ae; Lee, Sang In; Rubinelli, Peter M.; Roto, Stephanie M.; Pavlidis, Hilary O.; McIntyre, Donald R.; Ricke, Steven C. (Frontiers in Microbiology, 2017)
Feed supplements are utilized in the poultry industry as a means for improving growth performance and reducing pathogens. The aim of the present study was to evaluate the effects of Diamond V Original XPCTM (XPC, a fermented product generated from yeast cultures) on Salmonella Typhimurium ST 97 along with its potential for modulation of the cecal microbiota by using an anaerobic in vitro mixed culture assay. Cecal slurries obtained from three broiler chickens at each of three sampling ages (14, 28, and 42 d) were generated and exposed to a 24 h pre-incubation period with the various treatments: XPC (1% XPC, ceca and feeds), CO (ceca only), and NC (negative control) group consisting of ceca and feeds. The XPC, CO and NC were each challenged with S. Typhimurium and subsequently plated on selective media at 0, 24, and 48 h. Plating results indicated that the XPC treatment significantly reduced the survival of S. Typhimurium at the 24 h plating time point for both the 28 and 42 d bird sampling ages, while S. Typhimurium reduction in the NC appeared to eventually reach the same population survival level at the 48 h plating time point. For microbiome analysis, Trial 1 revealed that XPC, CO and NC groups exhibited a similar pattern of taxa summary. However, more Bacteroidetes were observed in the CO group at 24 and 48 h. There were no significant differences (P > 0.05) in alpha diversity among samples based on day, hour and treatment. For beta diversity analysis, a pattern shift was observed when samples clustered according to sampling hour. In Trial 2, XPC and NC groups exhibited the highest Firmicute level at 0 h but the Bacteroidetes group became dominant at 6 h. Complexity of alpha diversity was increased in the initial contents from older birds and became less complex after 6 h of incubation. Beta diversity analysis was clustered as a function of treatment NC and XPC groups and by individual hours including 6, 12, 24 and 48 h. Overall, addition of XPC influenced microbiome diversity in a similar fashion to the profile of NC group.